Peran Koperasi Unit Desa Terhadap Peningkatan Kesejahteraan Anggota - Amruh Amruh; Rahmayati Rahmayati (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The essence of cooperatives is cooperation, namely cooperation between members and administrators in the context of realizing the welfare of members and the community, as well as building the national economic order. This study aims to determine the role of cooperatives in improving the welfare of members of the Kuala Tunak Tabuyung Cooperative and to determine the factors that hinder the welfare of members of the Kuala Tunak Tabuyung Village Unit Cooperative, as well as to determine the plasma core partnership as a means of impetus in improving the welfare of the members of the Kuala Tunak Tabuyung Cooperative so that it can be distributed equally. This research method uses a qualitative descriptive approach. The results of this study indicate that the role of the Kuala Tunak Tabuyung Village Unit Cooperative in improving the welfare of members produces positive results. Because with the plasma core partnership that exists between KUD Kuala Tunak Tabuyung and PT Sawit Sukses Sejati, it has a good impact on the welfare of members. With plasma management, it can open new jobs for the community and open up opportunities to open new businesses for members and the community in Tabuyung Village.